Planned factory outlet centres in Germany - Kleine, Klaus; Offermanns, Thomas (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
The sheer number of planning applications for factory outlet centres, representing for Germany a new type of commercial operation, and the impacts such developments are feared to exert have placed FOC at the centre of a controversial and frequently extremely heated debate. The paucity of the information currently available on projects currently in the planning stage in Germany provided the starting point for a diploma dissertation submitted to the Faculty of Spatial Planning at the University of Dortmund with the title “Prospects of Factory Outlet Centres in Germany”. At the centre of this study was an empirical analysis (completed in March 1999) of the centres currently in planning. The findings of this study are reported in this article; however, in view of the rapid pace of developments in this field, in some respects the study has to be seen as no more than a snap-shot.
Keywords: Article